Impact of Phytase-Supplemented Palm Kernel Cake on Growth, Feed Efficiency, and Economic Viability in Poultry - Ewur Banson Kwamina; Abotsinah Gabriel; Yao Osae Michael; Alhassan Kusi Khalid; Amoah Obeng Elias; Azure Samuel; Naa Borley Dromo Ashong Evangeline; Yaw Segbedzi Van-Dyck Norbert; Isaac Kobina Philbert (Journal of Farming, 2025)
The rising costs of conventional poultry feed ingredients, such as soybean, maize, and fish meal, have prompted the search for more affordable and sustainable alternatives in poultry production. This study investigates the use of phytase-supplemented Palm Kernel Cake (PKC) as a replacement for soybean meal to improve feed efficiency, nutrient absorption, and growth performance in poultry. White Leghorn layers, Rhode Island Red layers, broilers, and cockerels were fed three different feed formulations: conventional feed (CF), Moderate PKC with Phytase (MPP), and High PKC with Phytase (HPP). The results showed that PKC-based diets significantly reduced feed costs while maintaining satisfactory growth, although CF led to higher body weight gain and feed efficiency. The MPP formulation struck an optimal balance between cost savings and nutritional quality, making it a viable option for layers and cockerels, while CF remained the most effective for broilers. While the HPP formulation resulted in lower feed costs, it compromised weight gain and overall profitability. These findings highlight the potential of phytase-enhanced PKC as a sustainable, cost-effective alternative to conventional feed, particularly in regions with high feed costs. However, the study emphasizes the importance of balancing cost reductions with feed quality to maximize profitability. Future research should focus on optimizing PKC inclusion levels and exploring additional enzyme supplements to further enhance feed efficiency and support sustainable poultry farming practices. This study provides valuable insights into how strategic feed formulation can support both economic and production goals in the poultry industry.
Keywords: Phytase